The perceived benefits derived from visits to a super regional shopping centre: An exploratory study - Nic S. Terblanché (South African Journal of Business Management, 1999)
Studies that aim to identify shopper types typically attempt to identify a limited set of differentiated shopper types to which retailers can target differentiated marketing efforts. The identification of shopper segments patronising large shopping centres. have been surprisingly underresearched. This study investigated the perceived benefits of shopping at a large super regional shopping centre and three distinct benefit dimensions emerged.
Keywords: 650